Coach evaluation from three perspectives: An athletic director, a coach and a consultant, a commentary - Huber, J. (International Sport Coaching Journal, 2015)
Commentary to a paper, written by Gilham, Hansen and Brady (more commentaries pp 203-212): Coaches are evaluated and judged on a large number of factors (Gillham, Burton, & Gillham, 2013). The purpose of this paper is to describe the views of three different professionals on coach evaluation. An athletic director and a coach from different Canadian colleges and a coaching consultant responded to the same series of questions regarding coach evaluation at the college level. Across the three professionals, the views expressed are more similar than dissimilar, with each professional emphasizing a different piece of the coach evaluation process. The information presented aligns both with coaching standards in the United States and at the International level. Stakeholder views are compared with the coaching science literature and recommendations for athletic directors and coaching scientists are provided.